Present vs. Future Property Losses From a 100-Year Coastal Flood: A Case Study of Grand Isle, Louisiana - Mostafiz, Rubayet Bin; Bushra, Nazla; Rohli, Robert V.; Friedland, Carol J.; Rahim, Md Adilur (Frontiers in Water, 2021)
Louisiana, U.S.A., is among the world’s most vulnerable places to coastal flooding. Although many factors exacerbate this hazard in Louisiana, land subsidence from compaction of marshlands and underground resource extraction, shoreline erosion accelerated by eustatic sea level rise (ESLR), and tropical-cyclone-induced storm surge are three of the most important. Increasing frequency and intensity of natural hazards under climate change scenarios are expected to exacerbate the coastal flood risk. While past research has focused on flood risk assessment and mitigation strategies, including climate change scenarios, few studies examine all of these factors in concert. This study shows calculations of present flood depths and considers additional coastal subsidence, ESLR, and tropical-cyclone-induced storm surge under climate change scenarios developed by Louisiana’s Coastal Protection and Restoration Authority (CPRA) to estimate present and future flood losses (2020) to structures and their contents at the individual building level in Grand Isle, Louisiana, a barrier island town of immense ecological, economic, historical, recreational, cultural, and aesthetic treasure. Results suggest that the average 100-year flood depth in buildings will increase by 41cm by 2050, with subsidence contributing over 82 percent of this total. Subsidence is projected to escalate structure and content losses by 17 percent above losses in 2017, while ESLR may contribute three percent above 2017 losses. A 100-year tropical-cyclone-induced storm surge event amid a “low” scenario of environmental change as defined by CPRA would increase Grand Isle’s structure and content losses by 68–74 percent above the 2017 value in ten years, 141–149 percent in 25 years, and 346–359 percent in 50 years. The most drastic (“high”) scenario of environmental change as defined by CPRA would increase the 100-year storm surge losses by 85–91 percent above the 2017 value in ten years, 199–218 percent in 25 years, and 407–415 percent in 50 years. Outcomes from this study will offer a more realistic risk assessment model and will direct flood risk managers, property owners, and other stakeholders to build a comprehensive framework to minimize future flood risk in one of the most vulnerable sites in the U.S.A. to coastal flooding.